Religiusitas dan Pengetahuan Terhadap Sikap dan Intensi Konsumen Muslim untuk Membeli Produk Kosmetik Halal - Ajeng Larasati; Sri Rahayu Hijrah Hati; Anya Safira (Esensi: Jurnal Bisnis dan Manajemen, 2018)
Religiousity and Knowledge to Attitude and Intention of Muslim Consumers to Buy Halal Cosmetics GoodsThis study discusses the influence of religiosity and knowledge on the attitude and intention of Muslim consumers to buy cosmetic products with halal positioning. The object of this research was a local cosmetic brand that uses halal positioning. Data was collected through a survey of 217 respondents with judgmental sampling technique. The respondents were Muslim women who have never made a purchase and use cosmetics that became the object of research. The results show that religiosity and knowledge have positive and significant effects on consumer attitude to buy a cosmetic product with halal positioning. However, the influence of religiosity on consumer attitudes is much greater than the influence of knowledge on consumer attitudes towards cosmetics with halal positioning. This study also shows that consumer attitudes have a significant positive effect on consumer intentions to buy cosmetics with halal positioningDOI: 10.15408/ess.v8i2.7459